Quality of life of 26 family members from four generations with X-linked hypophosphatemia: a cross-sectional study - Alsagheir, Afaf I.; Bin-Abbas, Bassam; Alghamdi, Nujud M.; Alhuthil, Raghad T.; Murad, Sarah A.; Husein, Tala H.; Mughal, M. Zulf; Alsabban, Zehour E.; Almarzoug, Layla M.; Ramzan, Khushnooda (Frontiers in Endocrinology, 2025)
IntroductionX-linked hypophosphatemia (XLH) is a lifelong, progressive genetic condition affecting patients’ physical health and quality of life.MethodsThis cross-sectional study aimed to understand the burden of XLH on four generations of family members with XLH. 26 family members with XLH from Saudi Arabia were assessed via a home visit and clinical assessment in hospital. Patient demographics, biochemical parameters, and radiological and skeletal ndings were collected. Quality of life was assessed using the 36-Item Short Form Survey (SF-36) and Pediatric Quality of Life Inventory (PedsQL 4.0). Further assessment involved the 6-minute walk test (6MWT) and Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain assessment.ResultsOur results showed low quality of life for the adults and children, with mean SF-36 and PedsQL (8–18 years) scores of 34.12 (standard deviation [SD] 25.02) and 55.04 (SD 29.47), respectively. High levels of complications of XLH and surgical interventions were common, including dental abscesses (92%), tooth loss (73.07%), osteotomies (76.92%) and craniosynostosis (76.90%). In 15 adult patients, aged 35–55 years, moderate WOMAC scores for pain, stiffness, and function of hip and knee joints and low 6MWT scores were reported. Skeletal deformities in the hip (53.85%) and skull (76.90%), and fractures and pseudofractures (38.40%), were common among older patients.DiscussionThese ndings demonstrate that the burden of XLH in these family members who had delayed diagnosis and were non-compliant to medical treatment and supportive care was high. Greater awareness and early diagnosis are essential for identi cation of cases and early initiation of treatment.